analisis pendapatan dan kelayakan usaha peternakan ayam broiler di desa karangmangu kecamatan ngambon kabupaten bojonegoro - Nadia, Nadia Tri Anjani (Oryza : Jurnal Agribisnis dan Pertanian Berkelanjutan, 2023)
This study aims to analyze the income and feasibility of broiler chicken farming in Karangmangu Village, Ngambon Sub-district, Bojonegoro Regency. Broiler chicken farming was chosen due to its promising prospects with rapid growth and high market demand. This research employs a survey method with purposive sampling technique, involving 4 broiler chicken farmers as respondents. The data collected includes fixed costs, variable costs, revenues, and net income. The results indicate that the average total revenue per period is IDR 930,000,000 with an average total cost of IDR 705,073,719. The average net income per period is IDR 224,926,281. Feasibility analysis using the R/C ratio shows an average value of 1.323, indicating that the business is feasible to run. The study concludes that broiler chicken farming in Karangmangu Village is financially profitable and feasible for development. Keywords: Income, Business Feasibility, Broiler Chicken Farming, Karangmangu Village, Ngambon Sub-district